Cold plasma catalysis as a novel approach for valorisation of untreated waste glycerol. Issue 11 (11th May 2018) - Harris, Jonathan; Phan, Anh N.; Zhang, Kui
Abstract : Waste glycerol decomposition to valuable products at high conversion and selectivity in a non-thermal plasma reactor. Abstract : Glycerol, a by-product from biodiesel production, is currently considered as waste for disposal. Several attempts have been made to convert this wasted resource for high-value added products via either chemical or biological processes. However, complex steps are required to remove impurities and the selectivity of desired product(s) is low. In this paper, cold plasma catalysis was for the first time proposed to valorise untreated waste glycerol, greatly reducing the negative environmental impacts of waste glycerol. The attractiveness of this approach is that the process can be easily tuned toward specific products with high yields with a very short reaction time (around 16 seconds) at near ambient conditions. By altering the carrier gas, cold plasma power and packing material/catalyst, up to 99% of untreated waste glycerol was converted into either gas products consisting of hydrogen (55 mol% or 7.02 wt%), hydrocarbons (C1 –C4 : 9–10 wt%), CO (19 wt%) and CO2 (16 wt%), or high value liquid products such as acetol (up to 54 wt%). The findings of this work could open up new opportunities for intensification of green chemical processes and biorefining of waste materials by reducing pre-treatment steps, solvent requirements and amount of waste generation.